Air‐Pressure‐Assisted Pen‐Nib Printing for 3D Printed Electronics (Adv. Mater. Technol. 6/2022). Issue 6 (7th June 2022) - Ahn, Jinhyuck; Sim, Ho Hyung; Kim, Je Hyeong; Wajahat, Muhammad; Kim, Jung Hyun; Bae, Jongcheon; Kim, Seonghyeon; Pyo, Jaeyeon; Jeon, Chang Jun; Kim, Bum Seok; Baek, Sung Hyun; Seol, Seung Kwon
Abstract : Functional Ink Ejection Air‐pressure‐assisted pen‐nib printing approach can control the functional ink ejection by negative (suction, red arrow) and positive (ejection, blue arrow) air pressure as shown in article number 2101172 by Seung Kwon Seol and co‐workers. This new conceptual printing method can produce electrical and functional components with various material inks on non‐flat and 3D surfaces, contributing to realize the 3D printed electronic devices.